Kedudukan Hukum Anak Perusahaan Badan Usaha Milik Daerah - Sigit Somadiyono (Wajah Hukum, 2021)
Subsidiary is a company that was born due to the transfer or participation of majority shares by another company or it is called the parent company. There are no regulations related to subsidiaries in the laws and regulations related to companies or regarding Regional Owned Enterprises. This has resulted in confusion regarding the position of the regional-owned company subsidiaries, especially the unclear position of state finances in the subsidiary companies. The problem in this research is what is the legal status of ownership of a regional-owned company subsidiary? And what is the responsibility of the holding company of a Regionally Owned Company to its subsidiaries? The purpose of this study was to determine the legal status of the subsidiary and the responsibilities of the Regional Owned Company as the holding company. The research method used is normative juridical analysis of the laws and regulations and the theory of the jurists. From the results of the research, it is found that even though the status is a subsidiary of a Regional Owned Enterprise, the subsidiary is not owned by the Regional Government but has a private or private status, so that there is no special binding legal relationship between the Regional Government as a shareholder of a Regional Owned Enterprise and its owned subsidiary Regional owned enterprises. The responsibility of a Regional Owned Company as the holding company with its subsidiary is limited to the relationship between the shareholders and the company as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies.